Constrains in the articulation between profession, family, and personal life: a case study of the Portuguese police (PSP) - Rocha, Ana; Espírito Santo, Paula; Ferreira, Ana Paula (Frontiers in Sociology, 2024)
The dangers and stresses of a police officer’s career cause physical and psychological distress which in turn cause considerable challenges for the integration of professional, family, and personal life. This study focuses on the conditions that influence this articulation between the personal, family, and professional lives of Portuguese Police (PSP1) officers. A questionnaire survey was applied to 414 police officers from 11 divisions of COMETLIS.2 At the empirical level, several models were tested to assess the articulation between the professional, family, and personal lives of police officers. The results highlight the influence of having young children, elderly people or other dependents living in the family home, as well as the employee’s age, on the job’s interaction with professional life. At a professional level, the variables shift work, professional category, years of service and working away from home were identified by the officers as conditioning factors in the work-family-personal life balance. Sex differences in the articulation of professional, family, and personal life were also observed.